Policies to Promote Angel Investment in Startups in Some Countries in Southeast Asia - Thi Kim Anh, Nguyen; Thanh Dat, Dang (VNU Journal of Science: Policy and Management Studies; Vol 37 No 1, 2021)
Angel investor plays an important role in the startup ecosystem, and is a factor that fills the capital gap for startups and also brings many benefits to startups when they can accompany and support expertise, management and consulting for startups. In the early stage of establishment and development of the startup ecosystem, the role of governments was important in issuing policies and providing solutions to promote angel investment. For Vietnam, encouraging angel investors to invest in startups is an important policy in developing the startup ecosystem. With research on policies to promote angel investment in startups in some countries in Southeast Asia including: Singapore, Thailand and Malaysia, the article summarizes some experiences to promote angel investment in startups in Vietnam. Keyword: Angel investor, startup. References [1] Investopedia, Angel Investor, https://investopedia.com/terms/a/angelinvestor.as, 2020 (accessed on 03/9/2020). [2] Startup SG, Overview Singapore’s Startup Ecosystem, https://www.startupsg.gov.sg/, 2020 (accessed on 03/9/2020). [3] WTO and International Trade Center - VCCI, research report: Mechanism to support Innovative Startups: International Experience – Proposed solutions for Vietnam, https://wtocenter.vn/an-pham/13265-study-mechanism-to-support-innovative-startups-international-experience---proposed-solutions-for-vietnam, 2017 (accessed on 03/9/2020). [4] Kam, W.P. Overview of angel investing in Singapore, Tech in Asia, https://www.techinasia.com/overview-of-angel-investing-in-singapore/, 2011 (accessed on 03/9/2020). [5] Enterprise Singapore, SEEDS Capital - Enterprise Singapore, https://www.enterprisesg.gov.sg/financial-assistance/investments/investments/seeds-capital/overview, 2020 (accessed on 03/9/2020). [6] Guide Me Singapore, Singapore Tax Deduction Scheme for Angel Investors, https://www.guidemesingapore.com/business-guides/taxation-and-accounting/personal-tax/tax-deduction-scheme-for-angel-investors, 2020 (accessed on 03/9/2020). [7] Startup Angels, Bangkok Startup Angels, https://startupangels.com/market/bangkok/, 2017 (accessed on 03/9/2020). [8] Embassy of the Kingdom of the Netherlands in Bangkok, Startup Ecosystem Thailand, www.nederlandenu.nl›startup-thailand-factsheet, 2019 (accessed on 03/9/2020). [9] DFDL, Thailand Tax Update: New Tax Incentives for Angel Investors, Jonathan Blaine, https://www.dfdl.com/resources/legal-and-tax-updates/thailand-tax-update-tax-incentive-for-angel-investor/, 2018 (accessed on 03/9/2020). [10] Ajagbe Akintunde Musibau, Ismail Kamariah, The Financing of Early Staged Technology Based Firms in Malaysia, Middle-East Journal of Scientific Research (2013) 18 (5): 697-707, DOI: 10.5829/idosi.mejsr.2013.18.5.11747 [11] Malaysian Business Angels Network, 2018 Annual Report, https://mban.com.my/wp-content/uploads/ 2019/05/Annual-Report.pdf, 2019 (accessed on 03/9/2020). [12] Malaysian Business Angels Network, Angel Tax Incentive, https://mban.com.my/angel-tax-incentive/, 2020 (accessed on 03/9/2020). [13] Malaysia Business Angel Network, Angel Investor Application Explanatory Notes and Guidance Note, https://mban.com.my/wp-content/uploads/2017/04/Angel-Application_ Explanatory-Notes.pdf, 2017 (accessed on 03/9/2020).